Urinary Epithelial Sodium Channel (EnaC) Level as A Diabetic Marker of Nephropathy in Type 2 Diabetes Mellitus with Hypertension - Heti Kus Erni; Nina Tristina; Agnes Rengga Indrati; Dewi Kartika Turbawaty (Faculty of Medicine, Universitas Padjadjaran, 2022)
Increased prevalence of diabetes mellitus (DM) leads to the increased of various complications including diabetic nephropathy, which can lead to the end stage renal disease (ESRD). The Epithelial sodium channel (ENaC), which is located in distal convoluted tubules, plays an important role in transepithelial sodium reabsorption for electrolyte homeostasis. Diabetes mellitus can cause changes in ENaC function which will interfere with kidney blood pressure control, worsening hypertension, and kidney injury that eventually may trigger diabetic nephropathy. The aim of this study was to determine the validity of urinary ENaC for screening diabetic nephropathy in type 2 diabetes mellitus (T2DM) with uACR as the gold standard. This was a cross-sectional analytical observational study conducted in Dr. Hasan Sadikin General Hospital Bandung, Indonesia, from December 2020 to July 2021. The subjects were 87 patients T2DM with hypertension with the majority of subjects (n=62) had a mean age of 56 years old and were experiencing albuminuria and hyperglycemia with DM for a duration of < 10 years. The poor glycemic control in these patients accelerated the occurrence of kidney damage. Result showed that urine ENaC level had a sensitivity and specificity of 82.3% and 48%, respectively, with 72.4% accuracy. The cut-off point of urine ENaC in this study was 0.98 ng/mL. Hence, urine ENaC level can be used as a test to screen for diabetic nephropathy with 82.3% sensitivity.